Behavioural risk-factors associated with the use of Facemask during Covid-19 pandemic lockdown period in Nigeria: online-based survey - Okondu, Ogechukwu, Emmanuel; Abubakar, Khadija; Olatade, Maitanmi Julius; Akingbade Oluwadamilare; Adesuyi Emmanuel O; Olugasa Babasola; Anyanwu Favour Chiamaka; Ekezie Modestina Amuche; Ifediora Uchenna Loveth; Arulogun, Oyedunni S; Okondu Chinedu Worlu (Student's Journal of Health Research Africa, 2022)
Background: The Coronavirus disease has rapidly become a public health challenge, with many countries adopting the usage of facemasks as one of the protective strategies against the virus. This study aimed to assess the behavioral risk factors associated with the use of facemasks during the Covid-19 pandemic lockdown period in Nigeria. Methods: The study recruited 500 participants in an online-based survey through a cloud-based platform called Google Forms. The main scales; facemask usage and behavioral risk factors were measured on a 0-27 and 0-24 point rating scale respectively, while the subscales are utilization, prevention, and perceived threats were measured on a 0-16, 0-19, and 0-5 point rating scale. Result: The usage of facemasks accounts for 32.8% (daily), 12.2% (weekly), 38.2% (monthly basis), and 16.8% use facemasks out of necessity. More than half (55.6%) use facemasks because of fear of punishment by the task force while challenges associated with the usage of facemasks include: difficulty breathing (47%) and suffocation (24%). A significant association was found between the use of facemasks and the prevention of COVID-19 (b= 0.029, 95% CI =0.055 - 0.114, p-value 0.049, r2=11.1%). Conclusion: The use of facemasks has become a norm and passed into law in Nigeria, however not a pleasant practice for most people Recommendation: Therefore there is a need for mass awareness and education to improve the use of facemasks in Nigeria.